The Role of Immunotherapy in Extensive Stage Small-Cell Lung Cancer: A Review of the Literature - Ioanna Tsiouprou; Athanasios Zaharias; Dionisios Spyratos (Canadian Respiratory Journal)
Lung cancer is the second most common cancer in both sexes worldwide. Small-cell lung cancer (SCLC) is a form of neuroendocrine tumor, which is classified into limited and extensive-stage disease and shows excellent initial response to chemotherapy; however, almost all patients relapse later. During the past few years, several clinical trials have evaluated the effect of addition of immunotherapy to conventional chemotherapy in patients with extensive SCLC. Checkpoint inhibitors are currently under investigation, especially the CTLA-4 and PD-1/PD-L1 inhibitors. Nowadays, evidence show a statistically significant survival benefit of adding atezolizumab, an IgG1 monoclonal antibody targeting against PD-L1, to platinum-based chemotherapy plus etoposide in patients who have not received any previous systemic therapy. Furthermore, the role of nivolumab, an IgG4 anti-PD-1 monoclonal antibody, is significant for the treatment of relapsed SCLC cases. Recently, pembrolizumab was the first immunotherapeutic agent to be approved by the FDA for patients with metastatic SCLC with disease progression on or after platinum-based chemotherapy and at least one other prior line of chemotherapy. Nevertheless, prognostic biomarkers to immunotherapy response remain to be discovered.